Re-vegetation of Gochar Lands for Fodder Production through Dairy Cooperative Society (DCS) - Singh, Digvijay; Sihag, Abhay; Choudhary, Alka; Uikey, Vinod (Indian Farming, 2020)
Proper scientific management by integration of feed, fodder and fuel crops in best way can enhance the productivity of village common lands or Gochar lands by 30%. Land development work needs to be done in order to make these lands cultivable and fencing ensures protection from stray animals. These lands are best managed by village institution (Gram Panchayat/ Dairy cooperative society) itself by producing fodder and selling it to landless or marginal dairy farmers at nominal price. It boosts the economy of rural areas by providing employment through dairying business by increasing the membership of dairy society and greater market access to all segments of society. Along with monetary benefits it also ensures environmental stability by plantation of tress at boundary. Such kinds of model need to be replicated at larger scale for better realization of benefits.